A description one of blooming cases on the Syrian coast opposite of Lattakia - Ikhtiyar, Samar; Durgham, Hani (Latakia University Journal -Biological Sciences Series, 2020)
In this study, the red tide was observed in the fishing and tourism port resulting from a significant increase in the abundance of species Heterosigma akashiwo and spp. Chattonella species from 15 May to 30 May 2018. The dynamic diversity of environmental Biological factors, including chlorophyll (chl a, temperature, salinity, pH, dissolved oxygen, chemical oxygen demand BOD520 , ammonium, nitrite, phosphorus (PO43-), silicate, and analysis during the brown tide at the fishing port and picnic for the first time in our Syrian coasts in the Yugoslav port area and compare them with offshore waters. In addition to studying the necessary dyes In different reference ways. The percentage of concentration of organic matter in which the sugars, proteins and lipids were studied, and the organic racism of carbon, nitrogen and phosphorides were studied. The concentration of heavy metals in the brown tide sample was also studied. The results indicated a high concentration of inorganic nitrogen due to the increased drainage of sewerage, which caused the rapid spread of the two species. Water temperature and nutrient concentrations were critical environmental factors. During the period between 15/5/2018 and 30/5/2018, according to the fishermen, we did not notice his presence except during our naval expedition during 28/5/2018. So we did a second test on 30/5/2018 and then disappeared completely. تم في هذه الدراسة رصد ظاهرة المد الأحمر في ميناء الصيد والنزهة الناتج عن زيادة كبيرة في غزارة أفراد النوع akashiwo Heterosigma و انواع من الجنس spp. Chattonella في الفترة من 15 أيار إلى 30 أيار 2018. تم تسجيل التغيرات الديناميكية للعوامل البيئية الحيوية واللاحيوية، بما في ذلك الكلوروفيل (Chl a)، درجة الحرارة، الملوحة، الأس الهيدروجيني (pH0)، الأوكسجين المنحل، الطلب الحيوي للأكسجين BOD205 ، شاردة النترات (No3-)، شاردة الأمونيوم (NH3)، شاردة النتريت (NO2-)، شاردة الفوسفات (3−PO4) ، السيليكات SiO42− ، وتحليلها خلال فترة المد الأحمر في ميناء الصيد والنزهة لأول مرة في شواطئنا السورية في منطقة الميناء اليوغسلافية، ومقارنتها مع المياه البعيدة عن الشاطئ، بالإضافة لدراسة الأصبغة اليخضورية بطرق مرجعية مختلفة. كما تمت دراسة غزارة الأجناس المسببة للمد الأحمر، وتحليلها بيوكيميائياً من خلال تحديد النسبة المئوية لكمية المواد العضوية فيها كالسكريات والبروتينات والليبيدات، والمادة العضوية العنصرية لكل من الكربون والآزوت والفوسفوريدات، بالإضافة لدراسة كمية نزر العناصر الثقيلة فيها. أشارت النتائج إلى ارتفاع كمية الآزوت اللاعضوي، بسبب زيادة صب مياه مجرور الصرف الصحي، ممّا سبب الانتشار السريع للأنواع المحددة، كما لعبت درجة حرارة المياه وكمية المغذيات كعوامل بيئية حرجة. ظهر المد الأحمر في فصل الربيع حيث غطّى منطقة الميناء التجاري وميناء الصيد والنزهة لمساحة لاتقل عن 2 كم2 خلال الفترة مابين 15/5/2018 و 30/5/2018 وقد قمنا بجولتي إعتيان خلال 28/5/2018 و 30/5/2018 واختفى بعدها المد الأحمر كليا.